Automatic document summarization - Chen, Fan (2019)
The information available online has been increasing exponentially and it is not going to slow down. The ability to extract information efficiently out from these huge data becomes crucial and necessary. As a result, document summarization as a part of Natural Language Processing (NLP), gains its attention by the machine learning community.